Ekstraversi dan Kompetensi Berbahasa Arab - Prabowo Adi Widayat; Muhammad Irham (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2021)
Language competency and extraversion relationships are certainly an important concern for every practitioner and conceptualist of Arabic learning. Such important concern is certainly based on understanding Arabic language competency and extraversion. Arabic language competency is an ability to enable Arabic productively and receptively optimized through listening, speaking, reading, writing, components, and structure of the language learned. Extraversion is the personality of a passionate individual, sociability to each other, social care in various events, assertive, courageous, and dominant in compound social interaction. These two components form a conceptual relationship by making Vygotsky's social constructivism the basis for constructing both of them in learning and global communication.